Pengembangan Multimedia Interaktif Berbasis Android Pada Mata Pelajaran IPAS Kelas V SD - Rosnidar; Fetri Yeni J; Zelhendri Zen; Zuwirna (Postgraduate, University of Mataram, 2026)
Learning Science and Social Studies (IPAS) in elementary schools still faces problems due to the dominance of conventional teaching methods, which result in low student engagement and difficulties in understanding abstract concepts. This condition highlights the need for more interactive learning media that align with students’ characteristics. This study aimed to develop Android-based interactive multimedia for the IPAS subject in Grade V elementary school and to examine its validity, practicality, and effectiveness. The study employed a research and development approach using the ADDIE model. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and learning outcome tests. The validation results showed that the developed multimedia was highly valid, with content validity of 92% and media validity of 88%. Practicality testing indicated that the product was very practical, obtaining scores of 83% from teachers and 80.2% from students. Effectiveness was measured by comparing pre-test and post-test scores, which increased from an average of 58.50 to 81.00, with an N-Gain value of 0.55 (moderate category). The findings indicate that the Android-based interactive multimedia is valid, practical, and effective in improving students’ learning outcomes in elementary school IPAS learning.